Urgensi Aplikasi Metode Qur’an Memorization Tool (Qmt) Sebagai Revolusi Dalam Menghafal Al-Qur’an - Abd Rozaq (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
The application method of the Quran Memorization Tool (QMT) is a way to implement a plan to memorize the Qur'an that has been compiled through software tools for OS XP and Android. This study wants to prove the urgency and success of the QMT application method in revolutionizing existing methods. This research is a descriptive-qualitative research which is included in the category of library research. The primary data in this study is the application of the Hafiz Quran Memorization Tool, while the secondary data are Be Hafiz, Verses, Verses of KSU, Hafidz Qur'an, Quran hafizhal-Qur'an memorization etc. The data collection technique used in this study is library research and the data analysis technique is content analysis in which the author attempts to describe the features in the application and then analyzes so that the advantages and disadvantages of the method are found and what distinguishes it from other applications. The results of this study are that there is a uniqueness possessed by the application of the Hafizh Quran Memorization Tool (QMT) method but not possessed by other application-based tahfizh methods, which lies in its comprehensive stages through planning, implementation and evaluation, while the Hafizh QMT method offers a revolution. method in memorizing the Qur'an, which is easy to memorize, fast process and strong memorization.